Health risks of cocaine adulteration: local anesthetics as modulators of monoamine and organic cation transporters - Kudlacek, Oliver; Senning, Niklas; Karden, Alexandra; Ludwig, Iina; Bicher, Julia; Kooti, Fatemeh; Holy, Marion; Stockner, Thomas; Luf, Anton; Sitte, Harald H. (Frontiers in Pharmacology, 2025)
Introduction Local anesthetics (LAs) are frequently used as adulterants in cocaine sold on the illicit market, sometimes in higher quantities than cocaine itself. These agents can mimic cocaine’s anesthetic effect, masking the products reduced purity. While reports suggest that LAs influence monoaminergic neurotransmission, systematic evidence remains limited. We examined three LAs commonly detected in cocaine samples submitted for drug checking from Vienna, Austriaprocaine, benzocaine, and lidocainefor their activity on uptake‐1 monoamine transporters (DAT, NET, SERT) and uptake‐2 organic cation transporters (OCT13).Methods and ResultsTransporter activity was measured in vitro, and computational docking was applied to explore molecular interactions with atomistic detail. Procaine and benzocaine inhibited DAT and NET at physiologically relevant concentrations, whereas neither compound affected SERT. Procaine also inhibited OCT1 and OCT2 with affinities comparable to or greater than cocaine, while benzocaine exhibited no OCT activity. Lidocaine had no significant effect on any transporter. Docking studies confirmed procaine binding within the DAT substrate pocket, consistent with its inhibitory profile.DiscussionAlthough LAs modulate uptake-1 and uptake-2 transporters, their actions are insufficient to replicate cocaine’s psychoactive effects. However, their impact on OCTs indicates potential health risks, highlighting the importance of accessible drug checking services for harm reduction.